Letrozole and palbociclib versus chemotherapy as neoadjuvant therapy of high-risk luminal breast cancer. (11th October 2018) - Cottu, P; D'Hondt, V; Dureau, S; Lerebours, F; Desmoulins, I; Heudel, P -E; Duhoux, F P; Levy, C; Mouret-Reynier, M -A; Dalenc, F; Frenel, J -S; Jouannaud, C; et al.
Abstract: Background: Palbociclib is a CDK4/6 inhibitor with demonstrated efficacy and safety in combination with endocrine therapy in advanced luminal breast cancer (LBC). We evaluated the respective efficacy and safety of chemotherapy and letrozole–palbociclib (LETPAL) combination as neoadjuvant treatment in patients with high-risk LBC. Patients and methods: NeoPAL (UCBG10/4, NCT02400567) is a randomised, parallel, non-comparative phase II study. Patients with ER-positive, HER2-negative, Prosigna ® -defined luminal B, or luminal A and node-positive, stage II–III breast cancer, not candidate for breast-conserving surgery, were randomly assigned to either letrozole (2.5 mg daily) and palbociclib (125 mg daily, 3 weeks/4) during 19 weeks, or to FEC100 (5FU 500 mg/m 2, epirubicin 100 mg/m 2, cyclophosphamide 500 mg/m 2 )×3 21-day courses followed by docetaxel 100 mg/m 2 ×3 21-day courses. Primary end point was residual cancer burden (RCB 0–I rate). Secondary end points included clinical response, proliferation-based markers, and safety. Results: Overall, 106 patients were randomised [median Prosigna ® ROR Score 71 (22–93)]. RCB 0–I was observed in four and eight patients in LETPAL [7.7% (95% CI 0.4–14.9)] and chemotherapy [15.7% (95% CI 5.7–25.7)] arms, respectively. Pathological complete response rates were 3.8% and 5.9%. Clinical response (75%) and breast-conserving surgery rates (69%) were similar in both arms. Preoperative Endocrine Prognostic Index 0 scores (breast cancer-specific survival) were observed in 17.6% and 8.0% of patients in LETPAL and chemotherapy arms, respectively. Safety profile was as expected, with 2 versus 17 serious adverse events (including 11 grade 4 serious AEs in the chemotherapy arm). Conclusion: LETPAL combination was associated with poor pathological response but encouraging clinical and biomarker responses in Prosigna ® -defined high-risk LBC. Contemporary chemotherapy regimen was associated with poor pathological and biomarker responses, with a much less favourable safety profile. LETPAL combination might represent an alternative to chemotherapy in early high-risk LBC. Clinical Trial Number: NCT02400567.